PRODEBAR ¿a strategic plan city? (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
The present investigation aims to establish if the Program for Strategic Development of Barquisimeto (PRODEBAS) complies with the methodology for the formulation of the Strategic Urban (PEU). While it is true that strategic planning has traditionally associated with organizational environments is helpful to understand how it has spread to urban areas. In this regard, we must recognize that the need for urban centers to adapt to the changes allowed the emergence of strategic planning as an instrument of city planning. In this context, this research was methodologically conceived as a descriptive method with field design, supplemented with elements of documentary source. The information was obtained through the techniques of literature review and expert consultation, using guided interviews with individuals directly inherent in the formulation of the program. The analysis showed that PRODEBAS but can not be classified as a USP, it has the virtue of being inspired by the philosophy of strategic planning. We conclude that this program, although it is inspired by the urban planning processes can not be considered a strictly strategic plan. However, it can be said that the city of Barquisimeto has initiated a development path that puts it on par with modern global trends in this area are carried out in recent decades to be able to undertake implementation of a legitimate proposal that meets the needs of the city.
Keywords: PRODEBAS; cities; strategic planning urban; municipalities